Knowledge development through regulation : a case study of the knowledge contribution of the public regulator to electronic bingo technology - Sibuyi, Johannes Zeni (Stellenbosch : Stellenbosch University, 2018)
Thesis (MA)--Stellenbosch University, 2018.